(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The topic presented in this article is quite relevant in the modern world. There are many different information technologies that allow you to improve listening, reading and writing skills when learning foreign languages, but not enough attention is paid to improving speaking skills. At the same time, it is important for the student to learn how to correctly pronounce sounds, words and entire sentences, as this is the basis for communication in the process of business and industrial relationships. In the modern pace of life, where every saved minute is valued, there is a need for language learning in a comfortable and convenient environment: at home, in a hotel, in the office. The widespread introduction of recognition technologies makes it possible to improve people’s skills in various fields of knowledge, among which teaching foreign languages occupies a special place. This article provides a brief overview of the work of speech- to-text conversion technology, determining the importance of speech recognition in modern conditions, as well as the relevance of creating a linguistic simulator for teaching the Uzbek language, taking into account the characteristics of the speaker.